(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Concrete is brittle and weak under tension, yet robust in compression. As soon as the concrete is poured, cracks begin to appear. Ordinary concrete is not allowed to be used in pavements since it causes ductility and breaking and failure. These flaws in concrete can be addressed by using fibers as reinforcement in the concrete mix.[1] Poly-ethylene and tire trash pollute the environment, resulting in a range of health problems. Poly ethylene and used tires may both be recycled and used as concrete fibers reinforcement. Poly-ethylene, as we all know, is a synthetic hydrocarbon polymer with features such as strength, shrinkage, ductility, and others. The effects of Poly-ethylene fibers addition on the characteristics of concrete are investigated in this paper. These fibers Poly-ethylene, and tire fibers; were chopped into little 30millimeter 6millimeter pieces and employed at a rate of 1.5 % by volume.[2] Concrete grades P–30, P–35, and P–40 were utilized. The concrete mix was designed in accordance with IRC– 45:2008. The strength characteristics of Poly-ethylene fibers reinforced concrete FRChave been written down and provided in the findings of this work. In the laboratory, shear and flexure strength were determined using a double shear test and a four-point bending test. There was an 18.10% increase in 28–day compressive strength, a 39.10% increase in flexure, and a 32.0% increase in shear strength. The trials revealed a 36.10% drop in deflection in the double shear test and a 22.10% decrease in the 4-point bending test. Theoretical study of deflections was carried out using energy techniques. Within the permitted boundaries, practical values were validated by theoretical values. Finally, it is possible to infer that tire and Poly ethylene may be employed efficiently in reinforced cement concrete.